2012
DOI: 10.1159/000341581
|View full text |Cite
|
Sign up to set email alerts
|

Mesial Temporal Astrocyte Tau Pathology in the MRC-CFAS Ageing Brain Cohort

Abstract: Background: Glial tau pathology is seen in certain tauopathies and in ageing. We determined its frequency in ageing mesial temporal lobe and its relationship to other tau pathologies in the MRC-CFAS population-representative neuropathology cohort. Methods: Mesial temporal lobe, including hippocampus, amygdala, entorhinal cortex and white matter, was examined using immunohistochemistry with the AT8 antibody to phospho-tau and RD3 and RD4 antibodies to 3R and 4R tau isoforms. Gallyas silver stain was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 35 publications
6
41
0
Order By: Relevance
“…Interestingly, a similar distribution of TSA was reported in aged baboons [55]. A study by the MRC-CFAS group confirmed the findings of Schultz et al and added that the TSA could be less commonly observed in the vicinity of neuronal cell bodies in gray matter areas such as amygdala and dentate gyrus [36]. Also, this study documented the 4R tau nature of TSA [36].…”
Section: Overview Of Astrocytic Tau Pathologies In the Aging Brainsupporting
confidence: 83%
See 3 more Smart Citations
“…Interestingly, a similar distribution of TSA was reported in aged baboons [55]. A study by the MRC-CFAS group confirmed the findings of Schultz et al and added that the TSA could be less commonly observed in the vicinity of neuronal cell bodies in gray matter areas such as amygdala and dentate gyrus [36]. Also, this study documented the 4R tau nature of TSA [36].…”
Section: Overview Of Astrocytic Tau Pathologies In the Aging Brainsupporting
confidence: 83%
“…A study by the MRC-CFAS group confirmed the findings of Schultz et al and added that the TSA could be less commonly observed in the vicinity of neuronal cell bodies in gray matter areas such as amygdala and dentate gyrus [36]. Also, this study documented the 4R tau nature of TSA [36]. Variable staining for Gallyas and p62 suggest that some of these astrocytes accumulate tau in a fibrillar state [3436, 38, 46].…”
Section: Overview Of Astrocytic Tau Pathologies In the Aging Brainsupporting
confidence: 72%
See 2 more Smart Citations
“…Astrocytic PHF-tau pathology in CTE is predominantly 4R tau immunopositive, but more widely distributed than that reported in the medial temporal lobe in aging and AD [103, 114]. Characteristically, the locus coeruleus shows neurofibrillary PHF-tau pathology in early stages of CTE, which can be substantial even in individuals under the age of 30.…”
Section: Adverse Neuropathological Outcomes Associated With Sports Pamentioning
confidence: 89%